2020
DOI: 10.2478/orhu-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the diet and breeding biology of the Common Barn-owl (Tyto alba) in a demographic cycle of Common Vole (Microtus arvalis) between two outbreaks×

Abstract: In the present study, we analysed the variation of breeding parameters and the diet composition of the Common Barn-owl (Tyto alba) in three different demographic phases of the Common Vole (Microtus arvalis) in a complete population cycle between two outbreaks. The study was conducted in the south-eastern part of the Transdanubian region in South Hungary. For the analysis, we used data of 81 randomly selected first clutches from 2015 to 2019, a time period which represented a full demographic cycle of the Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
(120 reference statements)
1
8
0
Order By: Relevance
“…Among murid rodents, Apodemus spp. were the most significant and their importance as an alternative prey was already described in several studies (Pezzo & Morimando 1995, Bontzorolos et al 2005, Rodrígez & Peris 2007, Horváth et al 2020). However, their relative frequency did not differ significantly between the two landscape types because the Wood Mouse and the Yellow-Necked Wood Mouse are not only associated with forests and forest edges but also occur in grasslands, hedgerows, field margins and agricultural areas (Fischer et al 2011, Torre et al 2015, Balestrieri et al 2017.…”
Section: Discussionmentioning
confidence: 57%
“…Among murid rodents, Apodemus spp. were the most significant and their importance as an alternative prey was already described in several studies (Pezzo & Morimando 1995, Bontzorolos et al 2005, Rodrígez & Peris 2007, Horváth et al 2020). However, their relative frequency did not differ significantly between the two landscape types because the Wood Mouse and the Yellow-Necked Wood Mouse are not only associated with forests and forest edges but also occur in grasslands, hedgerows, field margins and agricultural areas (Fischer et al 2011, Torre et al 2015, Balestrieri et al 2017.…”
Section: Discussionmentioning
confidence: 57%
“…Shrews are more typical prey for the Barn Owl (Tyto alba) [66][67][68] than for the Long-eared Owl. 22 These functional responses in diet to a changing availability of the main prey are wellknown in Long-eared Owls 29,30,69 and also in other owl species, such as the Barn Owl, 68,70,71 and other raptors which prefer an agricultural landscape. 72,73 Other prey species whose abundance increased only in some winters were a temporary supplementary prey.…”
Section: Discussionmentioning
confidence: 96%
“…In the south Transdanubian region of Hungary, where the recent study was carried out, barn owl (Tyto alba) is one of the most important vole specialist raptors. In a study between 2015 and 2019, the researchers established that the relative abundance of common vole in the diet of barn owls is 13–94% 41 . Another study found that in semi-natural and agricultural habitats, the frequency of occurrence of common vole in the birds’ diet was 35.6% and 57.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on burrow counting and pellet analysis, 2014 41 , 2016 38 , 2017 31 , and 2019 38 are labelled as common vole outbreak years. Small rodent populations have cyclic increase, peak and crash periods every 2–5 years.…”
Section: Discussionmentioning
confidence: 99%